2008
DOI: 10.1097/mnm.0b013e3283060c72
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and radiation dosimetry of [18F]F-PEB in nonhuman primates

Abstract: The effective radiation dose of [18F]F-PEB obtained from rhesus is similar to many other clinically utilized [18F] ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Extrapolation between various animal species is more reliable than extrapolation between animals and humans [19], but earlier studies have shown the usefulness of using animal biodistribution as a model for absorbed dose estimations in humans [31][32][33][34]. Using physiological time extrapolation improves the mean result.…”
Section: Discussionmentioning
confidence: 96%
“…Extrapolation between various animal species is more reliable than extrapolation between animals and humans [19], but earlier studies have shown the usefulness of using animal biodistribution as a model for absorbed dose estimations in humans [31][32][33][34]. Using physiological time extrapolation improves the mean result.…”
Section: Discussionmentioning
confidence: 96%
“…The difference between groups measured in this study was about 20%, which is encouraging. A delta of 20% is at least twofold higher than the coefficient of variation (CV) for [ 18 F]FPEB in the volumes of most potential interest, which tend to be less than 10%, and almost fourfold greater than the CV in the putamen, which is only about 5% …”
Section: Discussionmentioning
confidence: 99%
“…Fluorine‐18 ([ 18 F])‐3‐fluoro‐5‐[(pyridin‐3‐yl)ethynyl] benzonitrile ([ 18 F]FPEB) is one of several radiopharmaceuticals for noninvasively quantifying mGluR5 with positron emission tomography (PET) . [ 18 F]FPEB is a potent and highly specific antagonist . It has several characteristics shared by many useful biomarkers, including its relative ease of synthesis, physical half‐life, and a best‐in‐class kinetic energy associated with its positron.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of PET radiotracer development, agents targeting mGluR5 subtype have received the most attention . The most promising radiotracers include [ 18 F]‐FPEB, developed by Merck and [ 11 C]‐ABP688, a compound originally identified by Novartis (Figure ) . Recently, Wong et al .…”
Section: Alternative Targets For Positron Emission Tomography Imagingmentioning
confidence: 99%